2019
DOI: 10.1177/1079063219828779
|View full text |Cite
|
Sign up to set email alerts
|

Paraphilia and Antisociality: Motivations for Sexual Offending May Differ for American Whites and Blacks

Abstract: There has been little research on the sexual offending behavior of different racial groups. This study compares the characteristics and risk factors for American, non-Hispanic Whites ( n =797) and Blacks ( n = 788) who had been convicted of a sexual crime in New Jersey. The results indicated that Whites appeared more paraphilic whereas Blacks displayed higher antisociality. Despite the differences, however, the Static-99R, sexual recidivism risk tool, predicted equally well for both racial groups: Whites (area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 80 publications
3
15
0
Order By: Relevance
“…Noncontact offending was rare among the Indigenous individuals in the current study, and it is similarly rare for African Americans (Lee, Hanson, Calkins, & Jeglic, 2018).…”
Section: Discussionmentioning
confidence: 51%
“…Noncontact offending was rare among the Indigenous individuals in the current study, and it is similarly rare for African Americans (Lee, Hanson, Calkins, & Jeglic, 2018).…”
Section: Discussionmentioning
confidence: 51%
“…Most people with paraphilic interests do not have a mental disorder, and paraphilia is only clinically diagnosed when the paraphilic interest is recurrent, persistent, necessary for sexual enjoyment, and results in significant distress or impairment of functioning. Nevertheless, some studies found a significant positive relationship between antisociality (e.g., antisocial personality disorder, conduct disorder) and paraphilic interests and behavior, particularly in the criminal population (DeLisi, Drury, Caropreso, Heinrichs, Tahja, & Elbert, 2018;Lee, Hanson, Calkins, & Jeglic, 2020). The Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) identifies eight paraphilias and their associated paraphilic disorders (i.e., voyeurism, exhibitionism, fetishism, transvestic fetishism, frotteurism, sexual sadism, sexual masochism, and pedophilia; APA, 2013), while the International Classification of Diseases, Tenth Revision (ICD-10) recognizes six disorders of sexual preference (i.e., voyeurism, exhibitionism, fetishism, fetishistic transvestism, sadomasochism, and pedophilia;World Health Organization, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ethnicity and pedophilia/ASPD diagnoses. A previous study (Lee et al, 2019) found significant differences between African-American and White sex offenders in their frequency of ASPD versus pedophilia diagnoses and related measures. Lee et al (p. 19) found "…Blacks displayed higher general criminality (i.e., antisociality), whereas Whites appeared more paraphilic (i.e., pedophilic interests)."…”
Section: Analyses Involving Ethnicitymentioning
confidence: 84%
“…Some states accept it as a qualifying diagnosis, while others do not (e.g., New York). Lee and colleagues (Lee et al, 2019) suggests there may be ethnic differences in the frequency of paraphilic versus antisocial motives for sexual offending. Winters et al (2019) found lower kappa reliability for ASPD and other diagnoses, including antisocial personality disorder, kappa = .21; alcohol use disorder, kappa = .40; and borderline personality disorder, kappa = .54 (Freedman et al, 2013).…”
Section: Common Diagnoses and Diagnostic Reliability Of Mental Disord...mentioning
confidence: 99%